PENGARUH MODEL PEMBELAJARAN KOOPERATIF-STAD BERBANTUAN GAME KAHOOT TERHADAP HASIL BELAJAR SISWA - Nelly Yulida Lubis; Khairuna Khairuna (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to know the effect of cooperative learning model type Student Team Achievement Divisions (STAD) using smartphone game kahoot application toward students learning outcome. This research is quasi experimental design. The population of this study were students of class VIII SMP totaling 4 classes. The sampling was conducted by random sampling technique and obtained 2 classes as samples, class VIII-C and class VIII-D. Class VIII-C as the experimental class totaling 24 students and class VIII-D as the control class totaling 25 students. The test instrument used to determine student learning outcomes is a multiple choice questions in the form of pre-test and post-test which consists of 20 questions. The results showed that the class taught by STAD learning model using kahoot game obtained an average score of 82.917, while classes taught with conventional learning obtained an average score of 50.25. Hypothesis test obtained t count = 4.509 > t table = 4.047 then H0 is rejected and Ha is accepted. So it can be concluded that there is an effect on student learning outcomes through the Student Team Achievement Divisions (STAD) type cooperative learning model using the Kahoot game smartphone application on the learning outcomes of class VIII students on the Materials Structure and Function of Plants.